Retribution Revisited: A Reconsideration of Feminist Criminal Law Reform Strategies - Martin, Dianne L. (1998)
Were the last 30 years of feminist law reform activity around criminal justice misdirected? Or, if not misdirected, have the efforts been appropriated and manipulated by the New Right? This commentary reflects on this history, and on the failures of the retributive justice project generally, and argues for a reexamination of both. The discussion focuses on the tactics of the New Right and on the retributive goals of some victims' rights organizations as a means of highlighting the unintended consequences of key feminist initiatives around violence against women. Finally, the commentary identifies alternatives to retribution and a need for careful attention to the wider implications of all activism